Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional dan Kecerdasan Spiritual Terhadap Kinerja Pegawai: Studi Empiris pada Kantor Camat Demon Pagong - Susana Golan Hera; Hendrikus Herdi; Fransiscus De Romario (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to test and analyze the influence of intellectual intelligence, emotional intelligence, spiritual intelligence on employee performance at the Demon Pagong sub-district office. The research method used is a quantitative method. The population of this study was 89 people. The sample of this study was 48 employees who were the objects of this study. The data analysis used in this study was multiple linear aggression analysis. The results of this study indicate that intellectual intelligence (X1) and emotional intelligence (X3) have a positive effect on employee performance (Y) at the Demon Pagong sub-district office, while spiritual intelligence (X2) has a positive and significant effect on employee performance (Y) at the Demon Pagong sub-district office. While intellectual intelligence, emotional intelligence, spiritual intelligence all have an effect on employee performance.